ANALISIS SOSIOLINGUISTIK: VARIASI BAHASA DALAM GAYA KOMUNIKASI MAHASISWA PGSD UNIVERSITAS PENDIDIKAN INDONESIA KAMPUS PURWAKARTA - Kamiliya Nailah Fitri; Laras Ayu Syahrani; Sherina Herdiana Putri; Indah Nurmahanani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze language variation in the communication styles of students of the Primary School Teacher Education Program at Universitas Pendidikan Indonesia Purwakarta Campus through a sociolinguistic approach. The research employed a qualitative approach with a descriptive method. The subjects consisted of six students from the 2023 and 2024 cohorts selected using purposive sampling techniques. Data were collected through semi-structured interviews, non-participant observation, and documentation in the form of digital conversations and social media captions. Data analysis used an interactive model consisting of data reduction, data presentation, and conclusion drawing, while triangulation techniques were applied to ensure data validity. The findings indicate that students use flexible language variations depending on the context and interlocutors. In formal situations, students tend to use standard Indonesian, while in informal situations they frequently use slang, regional languages, and code-mixing with English. These language variations are influenced by socio-cultural backgrounds, peer environments, and social media influences. The use of language variation reflects students’ linguistic adaptability and communicative competence in various communication contexts. However, excessive use of informal language in academic settings needs attention to maintain effective, clear, and professional communication in learning activities.